Implementasi Metode Pembelajaran Contextual Teaching Learning (CTL) Untuk Meningkatkan Hasil Belajar Siswa Kelas VII SMP Pelita Harapan - M.Pd., Khoirudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2022)
This study aims to determine the effectiveness of applying the Teaching and Learning (CTL) learning method in improving student learning outcomes. The method used in this research uses class action research methods. The results showed that in cycle I and cycle II there was an increase in learning outcomes in class VII SMP Pelita Harapan students. So it can be concluded that the contextual learning method is effective for improving student learning outcomes.